Pendidikan Islam Terhadap Anak Dalam Presfektif Al-Qur’an (Pembentukan Karakter dan Kepribadian Muslim) - Rumina Rumina (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
Education is one of the tools to achieve a happy life both in the world and in the hereafter and through education can also lead us to error if wrong education is provided by parents, teachers and other education actors. So that only with Islamic education humans will live in peace, peace and happiness in the afterlife. Child education should begin as early as possible with religious education taught by the Qur'anic conception in a good and right way. Education starts from the womb until they are justified so that parents are separated from their responsibilities to them. The family is the child's first environment for learning. What is seen, heard and done in his family, will imprint on the child personally until they grow up so that education in the family determines their moral development when they are in another environment. Child coaching is carried out through, for example, good examples, attitude formation and training. character and personality of a person is formed from two side factors namely biological factors and environmental factors